2019
DOI: 10.1177/0899764019867774
|View full text |Cite
|
Sign up to set email alerts
|

International Volunteerism and Capacity Development in Nonprofit Organizations of the Global South

Abstract: Although international volunteerism has been a part of official development assistance for decades, the capacity development (CD) impacts of such programs in nonprofit organizations (NPOs) in the Global South have received scant attention. This article provides insights into the ways international volunteerism contributes to endogenous CD processes by analyzing survey and interview data collected from Australian volunteers and their host organizations in four countries. It shows that volunteers’ contributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…With regard to soft competencies, the literature has listed various soft competencies such as learning skills, negotiating skills, critical thinking, problem-solving and adapting to change skills ( Johnson and Thomas, 2007;Kühl, 2009), as well as leadership, administrative and financial skills (Bennett, et al, 2012). Schech, et al (2020) reported that it is widely recognised that both technical (hard) and functional (soft) capacities are needed to facilitate the capacity development of individuals. However, in practice, sometimes, there is no simple division between the 'soft' and 'hard' competencies because one type of skill may be included or combined with the others.…”
Section: Attributes Of Individual Capacitymentioning
confidence: 99%
“…With regard to soft competencies, the literature has listed various soft competencies such as learning skills, negotiating skills, critical thinking, problem-solving and adapting to change skills ( Johnson and Thomas, 2007;Kühl, 2009), as well as leadership, administrative and financial skills (Bennett, et al, 2012). Schech, et al (2020) reported that it is widely recognised that both technical (hard) and functional (soft) capacities are needed to facilitate the capacity development of individuals. However, in practice, sometimes, there is no simple division between the 'soft' and 'hard' competencies because one type of skill may be included or combined with the others.…”
Section: Attributes Of Individual Capacitymentioning
confidence: 99%
“…In addition, understanding the potential of IDVs to contribute to structural transformations that support women’s empowerment and gender equality requires more systematic research across program models. A more comprehensive focus on the perspectives of partner organization and community members, as well as an emphasis on the “processes from both sides of the volunteerism relationship,” is also needed to accurately understand the effects of IDV interventions (Schech et al, 2019, p. 4). In addition, more diverse voices and balanced perspectives on GEWE in IDV interventions require a careful analysis of their impact on systemic changes, structural inequality and discriminatory practices, and barriers to GEWE.…”
Section: Idvs’ Contributions To Gewementioning
confidence: 99%
“…Taken together, these theoretical approaches provide new lenses to investigate and document, from a subaltern perspective, whether the complementary contributions of international volunteerism truly support global partnership arrangements that can achieve end goals of gender equality (Schech et al, 2019). Drawing upon these diverse theoretical perspectives, this article explores the benefits and challenges of promoting gender equality through IDVs, specifically in programs focused on promoting women’s empowerment, improving women’s decision-making power, understanding women’s rights, and strengthening women’s enhanced skills development.…”
Section: A Theoretical Framework For Gender Equality In International Development Volunteeringmentioning
confidence: 99%
“…While the needs, challenges, and impacts of IDVs are increasingly mapped by researchers (Meneghini, 2016), less attention is given to how local staff are impacted by the presence of volunteers, and in particular the ways in which their regular work-roles are disrupted to help volunteers achieve their objectives. This local support may be critical to IDVs' success; yet, international volunteering research tends to view local staff primarily as beneficiaries of volunteers' capacity development efforts (Schech et al, 2020), without considering their role in helping VPOs to benefit from the volunteers' presence. This is important because directing local resources to support IDVs may contribute directly to organizational objectives and so to broader development outcomes like the United Nations' Sustainable Development Goals (Fee & Gray, 2020).…”
Section: Introductionmentioning
confidence: 99%